Matrix metalloproteinase‐14 (MMP‐14) downregulation inhibits esophageal squamous cell carcinoma cell migration, invasion, and proliferation. Issue 11 (15th September 2020) - Chen, Nanzheng; Zhang, Guangjian; Fu, Junke; Wu, Qifei
Abstract : Background: Matrix metalloproteinase‐14 (MMP‐14) is known to be a key regulator of oncogenesis and tumor progression. The present study was designed to assess the relationship between the downregulation of MMP‐14 and the in vitro proliferative, migratory, and invasive activity of esophageal squamous cell carcinoma (ESCC) cells. Methods: MMP‐14 expression in human ESCC and paracancerous normal esophageal tissue samples was evaluated via immunohistochemistry, and correlations between MMP‐14 staining and patient clinicopathological features were examined. In addition, siRNA was used to knockdown MMP‐14 in ESCC cells, and the proliferation and invasive activity of these cells were then evaluated via MTT and Transwell assays, respectively. Flow cytometry was additionally used to assess cell cycle progression, while Western blotting was employed to measure protein levels within these cells. Results: ESCC samples were found to exhibit MMP‐14 overexpression relative to paracancerous tissue samples, and this overexpression was positively correlated with tumor T classification (T1‐2 vs. T3; P  < 0.05), N classification (negative vs. positive; P  < 0.001), degree of differentiation (G1 vs. G3, P  < 0.05; G2 vs. G3, P  < 0.05) and clinical stage (I–IIA vs. IIB–III; P  < 0.05). When MMP‐14 was knocked down in ESCC cells, this induced cell cycle arrest, impairing their proliferative and invasive activity. Conclusions: MMP‐14 is a key regulator of the proliferation and invasion of ESCC cells, making it a viable therapeutic target for the treatment of this cancer. Abstract : The results of this study indicate that MMP‐14 upregulation commonly occurs in human ESCC and is correlated with to tumor T classification, N classification, degree of differentiation, and clinical stage of ESCC patients. MMP‐14 knockdown can additionally compromise the proliferative and invasive activity of these tumor cells, suggesting that MMP‐14 may be a viable therapeutic target for the treatment of ESCC, although further research will be needed to validate these findings. Furthermore, downregulation of the MMP‐14 expression level decreased cell proliferation and invasion ability.